Anak Didik Dalam Pendidikan Islam - Sukadji Sarbi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2013)
While is now various party progressively realise that sumberdaya's management nature and environmentally needs to mark sense a prevention of damage and sacrilege sort, to performed development on an ongoing basis. In this implementation effort a lot of experiences interference. One of amongst those to the fore has to be gotten things square an investment climate precisely, not only aims for economy behalf in common, but most importantly is how economic growth and social, society, and protection to natural resources damage nature and to prevent environment sacrilege